(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the cosmetic outcome of superficial facial lacerations repaired with single layer of non-absorbable monofilament suture and to observe time taken for closure and rate of infection and dehiscence. Study Design: Prospective case series study Place and Duration of Study: This study was conducted at the Accident and Emergency Department, Liaquat National Hospital, Karachi from 14th May 2009 to 31st January 2010. Materials and Methods: In our study we repaired 70 superficial lacerations presented within 24 hours to accident and emergency department; with single layer of 6/0 prolene suture. We restricted the age group from 18 to 40 because young individuals are more concerned about scars. Results: 36 patients presented within 3 hours of injury and among these 35 patients (97.2%) resulted in satisfactory outcome, 23 patients presented between 3 to 6 hours of injury and gave 95.7% satisfactory result while 11 patients presented after 6 hours and 7 patients (63.6%) gave satisfactory outcome. It indicates that repair of lacerations within 6 hours gives best outcome. Conclusion: Single-layer closure of nongaping, minor facial lacerations, with nonabsorbable monofilament suture yield satisfactory cosmetic outcome. Cosmetic outcome improved when repaired within 6 hours of injury but there is no impact of time on rate of infection and dehiscence